A noção de infância no Brasil na década de 1930: Uma análise da Revista Infância - Moura, Marina de (2007)
The purpose of this research is to analyze the notion of childhood present in Infância ( Childhood ), a magazine published in Brazil by Cruzada Pró-Infância (Crusade for Childhood), an institution devoted to fighting child mortality and illiteracy as well as promoting the education of children. Its target constituency was upper class mothers who helped the Crusade to fulfill its objectives among the lower classes. The magazine was published in the city of São Paulo, with irregular frequency, in the years 1935-1937. Approximately half of the articles were signed by renowned physicians, educators, and helpers. Usually the texts were illustrated with photos or drawings, and a large amount of space was given to advertising. Products for men, women and children were advertised in the magazine. During the three years 18 issues were published, of which 15 were analyzed for this research. During that time, only the last issues mentioned the editor. The subjects discussed in the magazine were intended to convey to the general public scientific information mainly in the areas of health and education. Its aim was to urge parents, educators, and those who were interested in children s life conditions to work towards a prosperous, healthy, and educated nation, under the mottos an educated country is a wealthy country and the children of today are the adults of tomorrow . Therefore we conclude that, in its use of scientific information for lay persons, Infância magazine was a progressive publication in which psychology and education were given great prominence and recognition